1995
DOI: 10.1109/59.476074
|View full text |Cite
|
Sign up to set email alerts
|

Fast decoupled power flow for unbalanced radial distribution systems

Abstract: This paper presents a novel power flow formulation and an effective solution method for general unbalanced radial distribution systems. Comprehensive models are considered including lines, switches, transformers, shunt capacitors, cogenerators, and several types of loads. A new problem formulation of three-phase distribution power flow equations taking into account the radial structure of the distribution network is presented. A distinguishing feature of the new problem formulation is that it significantly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
14

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(84 citation statements)
references
References 14 publications
0
70
0
14
Order By: Relevance
“…It is observed that the computed energy losses closely match ing the calculated energy (real time data) losses. The voltage profile for single and multiple placement using PSO Before_Min_V=0.8848 Rank= 5,4,7,6,11,10,17,16,14,13,12,15,23,8,9,32,3639,25,33,19,20,29,31,35,38,28,26,34,18,24,37,21,30,27,22 Rank= , 4,7,6,11,10,17,16,14,13,12,15,23,8, 9,32,36,39,25,33,19,20, The details of the distribution system are shown in Table VII. There are 5 interruption cases during the year 2011-2012 (Table IX).…”
Section: Results: (A)load Flow Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the computed energy losses closely match ing the calculated energy (real time data) losses. The voltage profile for single and multiple placement using PSO Before_Min_V=0.8848 Rank= 5,4,7,6,11,10,17,16,14,13,12,15,23,8,9,32,3639,25,33,19,20,29,31,35,38,28,26,34,18,24,37,21,30,27,22 Rank= , 4,7,6,11,10,17,16,14,13,12,15,23,8, 9,32,36,39,25,33,19,20, The details of the distribution system are shown in Table VII. There are 5 interruption cases during the year 2011-2012 (Table IX).…”
Section: Results: (A)load Flow Resultsmentioning
confidence: 99%
“…In this section, the development procedure will be described in detail. For distribution networks, the equivalent current-injection based model is more practical [5][6][7][8][9][10][11][12][13]. For bus, the complex load S is expressed by S i =P i +jQ i ------------(4) Where i = 1, 2, 3… N And the corresponding equivalent current injection at the -kth iteration of solution is …”
Section: Formulation Of Load Flow Model (A) Algorithm Developmentmentioning
confidence: 99%
“…[1][2][3][4][5]. Para peneliti ini telah mengusulkan metode atau teknik yang didasarkan pada skema iteratif Newton-Raphson.…”
Section: Tinjauan Pustakaunclassified
“…During the past decade, several power flow algorithms have been developed [1][2][3][4][5][6][7][8][9][10][11]. The most popular estimation algorithm is the forward/backward sweep based method for its fully utilizing the distribution network structure characteristics, simple programming, no large matrix calculation and fast computing speed [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%